Validity and reproducibility of a tripoding method in point registration-based 3D superimposition software compared to a conventional cephalometric method - Zakaria Nor Nadia; Wan Hassan Wan Nurazreena; Kamarudin Yasmin (Sciendo, 2022)
The present study aimed to assess the validity and reproducibility of a tripoding reference method for digital study cast superimposition to measure maxillary tooth movement.